Comprehensive Study: Building Community- Operated Renewable Energy Enterprise a Sustainable Energy Project for Barangay Kimbutan, Dupax Del Sur, Nueva Vizcaya - Khaled Al Hadi Lekhmaisi; Saleh Faraj Mansour2 (African Journal of Advanced Pure and Applied Sciences, 2023)
This study aimed to look into the socio-economic condition of the residents of Barangay Kimbutan in the Municipality of Dupax del Sur, province of Nueva Vizcaya after their homes were connected to the 7-kilowat (KW) Micro-hydropower plant built through the effort of the community in partnership with support organizations like SIBAT and the DOE. Data were gathered using actual visit to the barangay by the researcher wherein he interviewed the officials of the Barangay Council and certain municipal officials of Dupax Del Sur. To strengthen the information he obtained, he also gathered data from certain offices of the Local Government of the Municipality of Dupax del Sur. He also interviewed the head of the families in the barangay to gather information about the contribution of the micro-hydropower plant. This study found that the power plant was built in 2003 to generate affordable and adequate energy for lighting, agro-processing, livelihood activities, potable water and irrigation systems, and battery charging stations for the residents. The findings also disclosed that it has a positive improvement on the socio-economic development of the families in the barangay. But, the lack of technical and financial and entrepreneurial skills of the residents requires for an adoption of an off-grid energy technologies as well as training that will increase their entrepreneurial skill. The power generated from the plant sustained a minimum of 2.48 KW during summer and a maximum of 7KW during the rainy season. It is concluded that the 7-KW Micro-hydro power plant has positive impact on socio-economic status of the residents in Barangay Kimbutan. Thus, building a community-operated renewable energy enterprise can sustain the electricity need of rural communities. Based on thorough study and findings, the plant will continue to suffer due to lack of technical skill from the residents. Therefore, the government should provide enough energy-access plans and budgets for adoption of an off-grid energy technologies. Furthermore, residents should be taught entrepreneurial skill to increase the production and ensure stable income growth. Finally, local government should permit the current study to be used as a reference for further research about micro-hydropower system in the future.